The Impact of Bank Consolidation on Commercial Borrower Welfare - KARCESKI, JASON; ONGENA, STEVEN; SMITH, DAVID C. (Journal of Finance, 2005)
ABSTRACT We estimate the impact of bank merger announcements on borrowers' stock prices for publicly traded Norwegian firms. Borrowers of target banks lose about 0.8% in equity value, while borrowers of acquiring banks earn positive abnormal returns, suggesting that borrower welfare is influenced by a strategic focus favoring acquiring borrowers. Bank mergers lead to higher relationship exit rates among borrowers of target banks. Larger merger‐induced increases in relationship termination rates are associated with less negative abnormal returns, suggesting that firms with low switching costs switch banks, while similar firms with high switching costs are locked into their current relationship.